Ginsenoside Rd promotes glutamate clearance by up-regulating glial glutamate transporter GLT-1 via PI3K/AKT and ERK 1/2 pathways - Zhang eXiao (Frontiers in Pharmacology, 2013)
Ginsenoside Rd (Rd), one of the main active ingredients in Panax ginseng, has been showed to protect against ischemic cerebral damage both in vitro and in vivo. However, the underlying mechanism of Rd is largely unknown. Excessive extracellular glutamate causes excitatory toxicity, leading to cell death and neurodegenerative processes after brain ischemia. The clearance of extracellular glutamate by astrocytic glutamate transporter GLT-1 is essential for neuronal survival after stroke. Here we investigated the effects of Rd on the levels of extracellular glutamate and the expression of GLT-1 in vivo and in vitro. After rat middle cerebral artery occlusion (MCAO), Rd significantly increased the mRNA and protein expression levels of GLT-1, and reduced the burst of glutamate as revealed by microdialysis. Consistently, specific glutamate uptake by cultured astrocytes was elevated after Rd exposure. Furthermore, we showed that Rd increased the levels of phosphorylated protein kinase B (PKB/Akt) and phospho-ERK1/2 (p-ERK1/2) in astrocyte culture after oxygen-glucose deprivation(OGD). Moreover, the effect of Rd on GLT-1 expression and glutamate uptake can be abolished by PI3K/AKT agonist LY294002 or ERK1/2 inhibitor PD98059. Taken together, our findings provide the first evidence that Rd can promote glutamate clearance by up-regulating GLT-1 expression through PI3K/AKT and ERK1/2 pathways.